2008
DOI: 10.3347/kjp.2008.46.4.293
|View full text |Cite
|
Sign up to set email alerts
|

Malondialdehyde, Glutathione, and Nitric Oxide Levels in Toxoplasma gondii Seropositive Patients

Abstract: Abstract:The aim of this study was to investigate the difference in the serum malondialdehyde (MDA), glutathione (GSH), and nitric oxide (NO) levels between normal and T. gondii-infected patients. To this end, MDA, GSH, and NO levels in the sera of 37 seropositive patients and 40 participants in the control group were evaluated. In Toxoplasma ELISA, IgG results of the patient group were 1,013.0 ± ± 543.8 in optical density (mean ± ± SD). A statistically significant difference was found between patients and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 10 publications
12
48
0
Order By: Relevance
“…They also can bind to erythrocyte membranes, which are rich in polyunsaturated fatty acids (27), thereby causing membrane destruction and cellular damage (29). Karaman et al (33) reported that serum MDA concentrations were significantly increased in T. gondii-infected humans, and Yang et al (50) showed that serum concentrations of free oxygen radicals (NO, -OH, O2-) increased in T. gondii-infected mice. Our results are in accordance with Karaman et al (33), which suggested that erythrocyte MDA concentrations were significantly increased by T. gondii infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also can bind to erythrocyte membranes, which are rich in polyunsaturated fatty acids (27), thereby causing membrane destruction and cellular damage (29). Karaman et al (33) reported that serum MDA concentrations were significantly increased in T. gondii-infected humans, and Yang et al (50) showed that serum concentrations of free oxygen radicals (NO, -OH, O2-) increased in T. gondii-infected mice. Our results are in accordance with Karaman et al (33), which suggested that erythrocyte MDA concentrations were significantly increased by T. gondii infection.…”
Section: Discussionmentioning
confidence: 99%
“…Karaman et al (33) reported that serum MDA concentrations were significantly increased in T. gondii-infected humans, and Yang et al (50) showed that serum concentrations of free oxygen radicals (NO, -OH, O2-) increased in T. gondii-infected mice. Our results are in accordance with Karaman et al (33), which suggested that erythrocyte MDA concentrations were significantly increased by T. gondii infection. In contrast, Engin et al (23) found no change in serum MDA concentrations of mice infected with T.gondii.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The B-cell counts were markedly reduced in both men and women with toxoplasmosis [22]. Karaman et al [209] found a significantly higher serum NO levels in patients with latent toxoplasmosis as compared with seronegative controls, and Dzitko et al [210] demonstrated markedly increased serum prolactin (a strong immunomodulator) levels in women with latent T. gondii infection. Prolactin has been show to enhance production of IFN-γ, IL-12, and IL-10, but not of TNF-α, in a stimulus specific manner [211].…”
Section: Humansmentioning
confidence: 99%
“…[4,5] Toxoplasmosis can cause serious pathologies including hepatitis, pneumonia, blindness and severe neurological disorders. [6] Toxoplasmosis may cause severe disorders in immunocompromised patients and in Pregnant women, because of high risk of transplacental transmission and the occurrence of multiple congenital lesions in the fetus. [7] During infection, the immune effecter cells are able to kill or inhibit its intracellular growth.…”
Section: Introductionmentioning
confidence: 99%